Proactive personality and health literacy among patients with permanent colostomy: an observational study - Li, Wen; Zheng, Hui; Wang, Hai Bo; Jiang, Ye; Yang, Zhong Zhen; Lam, Soh Kim (Sciendo, 2025)
Objective: To investigate the distribution of health literacy (HL) levels and the association of HL with proactive personality in patients with permanent colostomy. Methods: A cross-sectional study was conducted to measure proactive personality and HL using validated scales. A total of 172 patients with permanent colostomy were selected from January 2021 to May 2022 in Yantai City, China. Descriptive statistics, t-test, ANOVA, Pearson correlation analysis, and multiple linear regression analysis techniques were used. Results: The results obtained from the study showed that the HL status of the participants was moderate. The correlation between participants’ total HL scores and proactive personality scores was 0.417 (P-value <0.001). In addition, HL showed statistically significant differences according to education level, place of residence, profession, and average monthly household income. Conclusions: This study showed that patients with higher proactive personality scores had higher HL. The key stakeholders require several positive strategies to improve the HL of patients with permanent colostomy by cultivating their proactive personalities, and these important policies will help to improve patient health and quality of life.